Microbial communities in aerosol generated from cyanobacterial bloom-affected freshwater bodies: an exploratory study in Nakdong River, South Korea - Kim, Jinnam; Lee, GyuDae; Han, Soyeong; Kim, Min-Ji; Shin, Jae-Ho; Lee, Seungjun (Frontiers in Microbiology, 2023)
Toxic blooms of cyanobacteria, which can produce cyanotoxins, are prevalent in freshwater, especially in South Korea. Exposure to cyanotoxins via ingestion, inhalation, and dermal contact may cause severe diseases. Particularly, toxic cyanobacteria and their cyanotoxins can be aerosolized by a bubble-bursting process associated with a wind-driven wave mechanism. A fundamental question remains regarding the aerosolization of toxic cyanobacteria and cyanotoxins emitted from freshwater bodies during bloom seasons. To evaluate the potential health risk of the aerosolization of toxic cyanobacteria and cyanotoxins, the objectives of this study were as follows: 1) to quantify levels of microcystin in the water and air samples, and 2) to monitor microbial communities, including toxic cyanobacteria in the water and air samples. Water samples were collected from five sites in the Nakdong River, South Korea, from August to September 2022. Air samples were collected using an air pump with a mixed cellulose ester membrane filter. Concentrations of total microcystins were measured using enzyme-linked immunosorbent assay. Shotgun metagenomic sequencing was used to investigate microbial communities, including toxic cyanobacteria. Mean concentrations of microcystins were 960 µg/L ranging from 0.73 to 5,337 µg/L in the water samples and 2.48 ng/m3 ranging from 0.1 to 6.8 ng/m3 in the air samples. In addition, in both the water and air samples, predominant bacteria were Microcystis (PCC7914), which has a microcystin-producing gene, and Cyanobium. Particularly, abundance of Microcystis (PCC7914) comprised more than 1.5% of all bacteria in the air samples. This study demonstrates microbial communities with genes related with microcystin synthesis, antibiotic resistance gene, and virulence factors in aerosols generated from cyanobacterial bloom-affected freshwater body. In summary, aerosolization of toxic cyanobacteria and cyanotoxins is a critical concern as an emerging exposure route for potential risk to environmental and human health.